Morphology and Molecular Analysis of Moesziomyces antarcticus Isolated From the Blood Samples of a Chinese Patient - Liu, Yuan; Zou, Ziying; Hu, Zonghai; Wang, Wenbo; Xiong, Jie (Frontiers in Microbiology, 2019)
Objectives: To identify the pathogen causing fungemia in a Chinses patient and describe its morphological and molecular characterizes. Methods: Samples of central and peripheral venous blood were collected for blood culture. Morphology and drug sensitivities of the isolated yeast-like fungus were analyzed. rDNA sequencing and molecular phylogenetic analysis of the isolated strains were performed using DNAMAN and MEGA software. Results: A strain of yeast-like fungi was repeatedly isolated from blood samples of a Chinese patient. The isolates grew well on sabouraud medium broth plate. The colonies were smooth and round at 28°C, and were of rough surface and irregular shape at 35°C. Molecular phylogenetic trees constructed based on the internal transcribed spacer (ITS) and D1/D2 domains of 28S rDNA gene demonstrated the isolated yeast-like fungus was Moesziomyces antarcticus. Drug susceptibility test showed that this isolated M. antarcticus was resistant or had relatively low susceptibility to flucytosine, fluconazole, voriconazole and itraconazole, and only sensitive to amphotericin. Conclusion: This study provided more information for the molecular and morphology characteristics of M. antarcticus and reviewed the species information of Moesziomyces associated with human infections, which will contribute to the identification and diagnosis of Moesziomyces infections.